PENGARUH PENERAPAN MODEL AKUNTANSI SEKTOR PUBLIK DAN SISTEM PENGENDALIAN INTERNAL TERHADAP UPAYA PENCEGAHAN FRAUD - Arimbi Fauziyah; Supanji Setyawan (Transpublika Publisher, 2023)
A system of accountants known as public sector accounting is utilized by public sector organizations. Threats to the administration of a public accounting might arise from the management structure that a business or organization has created for managing its enterprise. The threat of fraud is one of these. This review was conducted to determine the effect of the application of the public sector accounting model and internal control on fraud prevention efforts. This study uses a qualitative method with the use of previous research data. The results of the research in the form of analysis show that the application of the public sector accounting model has a positive effect on fraud prevention efforts. The results of the second analysis show a positive influence between internal control on fraud prevention efforts.